Transport properties and thermoelectric figure of merit of YBa2Cu3O7-x-Bi0.5Na0.5TiO3ceramics - Poom Prayoonphokkharat (2018)
© 2017 by American Scientific Publishers. The thermoelectric performance of YBa 2 Cu 3 O 7-x -Bi 0.5 Na 0.5 TiO 3 (BNT) ceramics was evaluated by the temperature dependence of electrical resistivity ρ(T), thermal conductivity κ(T) and Seebeck coefficient S(T) measurements. The (1-y)YBCO-(y)BNT ceramics with y= 0-0.07 were prepared by mixing powder of YBCO and BNT in the appropriate ratios. The powder mixture was pelletized and sintered at 900 °C for 2 h. Phase identification by X-ray diffraction showed that YBCO was the primary phase and the peak shift occurred due to lattice contraction. Scanning electron micrographs showed the microstructure to be anisotropic shape with a size range of 1.4-3.2 μm. The chemical composition within the sample seemed to be homogeneous in agreement with the result of phase analysis by XRD. The electrical resistivity of samples was found to increase with increasing in BNT concentration. The addition of BNT decreased the thermal conductivity due to more efficient phonon scattering by the substituted ions. From Seebeck coefficient measurement, small amount of BNT enhanced p-type Seebeck coefficient values but larger amount caused the major carrier transport mechanism to transform from p-type to n-type. The maximum ZT near 380 K was obtained in p-type YBCO and n-type (0.95)YBCO-(0.05)BNT compositions. These ceramics seem to be potentially suitable for an efficient thermoelectric unicouple.